2023
DOI: 10.3390/ma16041712
|View full text |Cite
|
Sign up to set email alerts
|

Hot Corrosion Behavior of TWAS and HVOF NiCr-Based Coatings in Molten Salt

Abstract: In order to extend the life of boilers by applying an anti-corrosion coating without the need to dismantle them, it is advisable to find coatings that can be applied using cheaper and portable techniques, such as Twin Wire Arc Spray technology (TWAS). In this study, we compare selected NiCr-based coatings and two uncoated steel substrates (steel 1.7715 and 1.4903). Two coatings, Cr3C2 - 25% NiCr and Hastelloy C-276 are deposited using High velocity oxygen-fuel technology (HVOF) and three coatings, NiCrTi, NiCr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Deepa Mudugal et al [8] & [9] performed the Cr 3 C 2 -NiCr coating on Superni 600 alloy and ascertained that Cr 3 C 2 -based feedstock powders are the right choice for coatings in components used in high-temperature erosion and corrosion environments. The authors reported in [10][11][12][13] studied the the effects of elevated temperatures on chromium-based coatings applied to boiler steels and nickel-based superalloys, particularly when exposed to a corrosive hot salt environment and found the accumulation of NiO and Cr 2 O 3 oxide layers on the coated surface. The existance of corrosion layer of oxide serves as an inhibitor to hinder the in ltration of the corrosive medium, hence impeding the oxidation of the entire coating.…”
Section: Introductionmentioning
confidence: 99%
“…Deepa Mudugal et al [8] & [9] performed the Cr 3 C 2 -NiCr coating on Superni 600 alloy and ascertained that Cr 3 C 2 -based feedstock powders are the right choice for coatings in components used in high-temperature erosion and corrosion environments. The authors reported in [10][11][12][13] studied the the effects of elevated temperatures on chromium-based coatings applied to boiler steels and nickel-based superalloys, particularly when exposed to a corrosive hot salt environment and found the accumulation of NiO and Cr 2 O 3 oxide layers on the coated surface. The existance of corrosion layer of oxide serves as an inhibitor to hinder the in ltration of the corrosive medium, hence impeding the oxidation of the entire coating.…”
Section: Introductionmentioning
confidence: 99%
“…Three samples of Cr3C2-25%NiCr (chromium carbide in a nickel-chromium matrix) HVOF coatings with a nominal composition of 70% Cr, 20% Ni, and 10% C (in wt%) were deposed to a 1.2376 high-speed steel substrate with dimensions of 15x20x14 mm [7]. The deposition was performed at the Research and Testing Institute Plzeň.…”
Section: Methodsmentioning
confidence: 99%
“…The durability and reliability of power generation equipment are important parameters affecting the stability of the energy market. In the case of components of combustion plants, such as boiler firewalls, heat exchangers, or pressure vessels of coal-fired power plants, the service life is often limited by the corrosion attack of an aggressive environment, where hot corrosion is especially a major issue determining the service life of said components [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Hot corrosion has been identified as a serious problem for many high-temperature aggressive environment applications, such as boilers [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 11 , 12 , 14 ], internal combustion engines, gas turbines [ 15 , 16 ], fluidized bed combustion boilers [ 17 ], industrial waste incinerators [ 18 , 19 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant substance known to promote hot corrosion processes is Na 2 SO 4 , mainly owing to its very good temperature stability in a wide range of oxygen partial pressures [ 7 ]. Na 2 SO 4 originates in oxidation reactions during the combustion of fuel containing both sulphur and sodium and possibly other alkali metals, such as potassium, which also form another corrosively aggressive sulphate attributed to the hot corrosion process—K 2 SO 4 [ 1 , 7 , 8 , 10 , 20 ]. Some other major aggressive substances known for their negative attribution to hot corrosion process are chlorides and vanadates [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%